Organisational Capabilities and Replicating Successful Programs Designed to Empower Poor Youths: A Correlational Study - Igbinakhase, Idahosa; Naidoo, Vannie (Journal of Economics and Behavioral Studies, 2018)
This article reports on the investigated relationship between the organisational capabilities of youth-serving non-governmental organisations (NGOs) and the replication of successful programmes designed to empower poor youths in Nigeria. The data used in this study were obtained from 187 youthserving NGOs in Nigeria registered with the Nigeria Network of Non-Governmental Organisations, the Conference of Non-Governmental Organisations (Edo State chapter), the Civil Society for HIV/AIDS in Nigeria (Edo State chapter) and the National Youth Council of Nigeria (Edo State chapter). Pearson’s correlation r was used to examine the relationship between the research variables and a positive relationship was found between the organisational capabilities of youth-serving NGOs and the replication of successful programmes designed to empower poor youths. In addition, regression analysis was used to determine the organisational capabilities of youth-serving NGOs that predicted the replication of successful programmes designed to empower poor youths in Nigeria, and it was found that adequate staffing, alliance-building, lobbying, replication and stimulating market forces significantly predicted the replication of successful programmes designed to empower poor youths in Nigeria. The study therefore recommends that appropriate measures be put in place by managers of youth-serving NGOs to ensure that the main predictors of the replication. Of successful programmes designed to empower poor youths are adequate to aid successfully in the replication of successful programmes designed to empower poor youths in Nigeria while also giving adequate attention to other organisational capabilities contained in the SCALERS model.